An Anti-Inflammatory Sterol Decreases Obesity-Related Inflammation-Induced Insulin Resistance and Metabolic Dysregulation - Chris L. Reading; Jaime Flores-Riveros; Dwight R. Stickney; James M. Frincke (Hindawi Limited, 2013)
Obesity-related inflammation-induced insulin resistance and metabolic dysregulation were investigated in retrospective analysis of placebo hematologic and metabolic laboratory data from trials associated with increasing chronic low-grade inflammation and body mass index. Studies included healthy subjects and those with progressive stages of metabolic dysregulation, including type 2 diabetes mellitus with uncontrolled hemoglobin A1c. Intrasubject variances in erythroid and metabolic values increased with metabolic dysregulation. Random effects were demonstrated in treatment-naïve diabetes for erythroid, glucose, and HbA1c fluctuations. The anti-inflammatory insulin sensitizer, HE3286, was tested for its ability to decrease obesity-related inflammation-induced insulin resistance and metabolic dysregulation in diabetes. HE3286 significantly decreased erythroid and metabolic variances and improved 1,5-anhydroglucitol (a surrogate of postprandial glucose) compared to the placebo group. HE3286 HbA1c decrease correlated with weight loss and inversely with baseline monocyte chemoattractant protein-1 (MCP-1) in metformin-treated diabetics. Normalization of HbA1c to the 84-day average hemoglobin revealed that HE3286 HbA1c decrease correlated with high baseline MCP-1 and MCP-1 decrease in treatment-naïve diabetics. HE3286 decreased insulin resistance, increased the frequency of decreased day 84 HbA1c in metformin-treated subjects, and decreased day 112 HbA1c in treatment-naïve diabetics. HE3286 may be useful to restore metabolic homeostasis in type 2 diabetes.